2022
DOI: 10.26434/chemrxiv-2022-ntd3r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MELLODDY: cross pharma federated learning at unprecedented scale unlocks benefits in QSAR without compromising proprietary information

Abstract: Federated multi-partner machine learning can be an appealing and efficient method to increase the effective training data volume and thereby the predictivity of models, particularly when the generation of training data is resource intensive. In the landmark MELLODDY project, each of ten pharmaceutical companies realized aggregated improvements on its own classification and/or regression models through federated learning. To this end, they leveraged a novel implementation extending multi-task learning across pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…This would allow partners to contribute more equally to the aggregated gradients. In the work of Heyndrickx et al (2022) it was however found that default weighting was more beneficial for the federated model.…”
Section: Compute Plansmentioning
confidence: 99%
See 3 more Smart Citations
“…This would allow partners to contribute more equally to the aggregated gradients. In the work of Heyndrickx et al (2022) it was however found that default weighting was more beneficial for the federated model.…”
Section: Compute Plansmentioning
confidence: 99%
“…MELLODDY Federated Learning (FL) Simulator During the MELLODDY project, many options were considered to improve the performance of the model (Heyndrickx et al 2022). In order to quickly assess each option, the partners conducted single partner studies.…”
Section: Platform Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…Federated learning has already been applied to drug discovery, as assessed by the recent outcomes of the MELLODDY project, which involved ten pharma companies, sharing federated information for a total of more than 21 million small molecules. , The MELLODDY approach uses multitask learning and underlying deep neural network architectures. In brief, local models were trained at each company, and only the gradients were exchanged, thus avoiding the disclosure of information on the underlying data and on the modeled end points.…”
Section: Introductionmentioning
confidence: 99%